Where Love Happens : Changing Social Practices of Love in the Long Nineteenth Century - Helene Grøn; Lene Østermark-Johansen; Victoria de Rijke (Peter Lang Ltd, International Academic Publishers, 2025)
Some decades ago, Jean-Luc Nancy asked, ‘Has not everything been said on the subject of love? … Could we perhaps be exhausted?'The question is a pertinent one; why devote yet another book to the subject? Grounding love in the realm of the concrete by querying, where does love happen?, the essays address hitherto under-researched aspects and aesthetics of love, like the love of the child, same-sex love, love of country, love for machines, controversial relationships, love of the dead, love of the past, and networks of relationships revolving around love and intimacy. Here, leading scholars suggest that changing social practices, developed in the course of the long nineteenth century, determined new spaces and places for love to happen, to unfold, develop – and break up. Thereby, the much-debated claim that romantic love is an invention of European Romanticism is challenged, asking if romantic love might not be less and other kinds of love far more romantic than at first imagined.